SINFLARGA AJRATISH MASALASIDA ALOMATLARNING INFORMATIVLIGINI BAHOLASH VA ULARNI TANLASH - Navruzov, E.R.; Maxarov, Q.T.; Raximova, M.A. (SCIENCE and SOCIETY, 2022)
This article discusses the dimensionality of reduction issue. To reduce the dimension was used the in formativeness of the features. Several methods were presented that are used to assess the in formativeness of features and the results were compared. The quality of feature selection was assessed with Naïve Bayes classifier.